Straightening light sheets. Issue 11 (November 2017) - Sáenz, Juan
Diffraction-free light-sheet beams, strongly confined in one axis, are typically thought to self-bend during propagation in free space and cannot be made flat. Now, diffraction-free planar light sheets in air have been realized by exploiting polychromatic pulsed beams.